English Partnering Efl Students With Chatgpt To Enhance Students’ Skills In Oral Communication - Agustina, Lia; Handoyo, Futuh; Damaryanti, Rita (Universitas Cokroaminoto Palopo, 2025)
The use of technology and robots in foreign language learning has gained popularity in recent years. The introduction of sophisticated artificial intelligence technology for language learning has the power to completely change the way that languages are taught and acquired. ChatGPT is an evolving language model created by OpenAI that can produce texts. ChatGPT may prove to be a useful tool for language learning for both educators and students. Artificial intelligence technology is transforming foreign language education by offering new pedagogical approaches. ChatGPT presents practical applications for both language instructors and students in educational settings. This study aimed to enhance students’ oral communication skills by partnering in which is a tool of ChatGPT. It answered the following questions: How can ChatGPT enhance students’ oral communication skills and also enhance students’ attitudes toward learning English. The findings reveal that large language models, such as ChatGPT, can substantially enhance English language learning through a multifaceted approach. Specifically, the research demonstrates that these AI-powered platforms facilitate language acquisition by (a) providing specific feedback on language accuracy and (b) fostering language fluency through ample contextual practice. The participants consisted of 25 students from the accounting management program at State Polytechnic of Malang. To sum up, it can be stated that ChatGPT contributed to students' success by enhancing their attitudes and verbal communication skills.